ICT BASED PLANETARIUM WITH EDUTAINMENT APPROACH IN MALANG CITY - Febryanti, Berliana (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, 2025)
Malang, with an area of 145.28 km² and the motto